Influencing Factors of the Continuous Usage Intention of Consumers of Online Food Delivery Platform Based on an Information System Success Model - Wang, Junbin; Shen, Xiangdong; Huang, Xinbei; Liu, Yuting (Frontiers in Psychology, 2021)
Online food delivery (OFD) has gradually become a development trend in the catering industry. However, the homogenization of the principal OFD platforms is becoming increasingly obvious, and there is an urgent need to explore consumers’ continuous usage intentions of the OFD platform. Unlike previous studies, the current study employs DeLone and McLean’s information system (IS) success model as the theoretical framework and constructs the influencing factors model of OFD platform users’ continued intention to use from three aspects: service, system, and information quality. Participants (N=361) completed a questionnaire assessing their OFD platform continuous usage intentions and results were analyzed using a structural equation model (SEM). Service worker, platform quality, and content consistency have significant positive effects on consumers’ trust in the platform and satisfaction. Consumers’ trust in the platform and satisfaction has a positive impact on their continuous usage intentions. We also explore the mediating effect of consumers’ trust in the platform and consumer satisfaction. This study adds to the academic literature and practical implications for consumers’ continuous usage intention. This study discusses the influencing factors and formation mechanism of consumers’ continuous usage intention and proposes a model of consumers’ continuous usage intention of OFD platforms. Moreover, OFD platforms can make differentiation strategies more targeted and eliminate the dilemma of homogenization competition of OFD platforms.